Multi-Center Development and Testing of a Simulation-Based Cardiovascular Assessment Curriculum for Advanced Practice Nurses. - Jeffries, Pamela R.; Beach, Michael; Decker, Sharon I.; Dlugasch, Lucie; Groom, Jeffrey; Settles, Julie; O'donnell, John M. (Nursing Education Perspectives (National League for Nursing))
Cardiovascular assessment skills are deficient among advanced practice nursing students, and effective instructional methods to improve assessment skills are needed. The purpose of this study was to develop, implement, and evaluate outcomes of a cardiovascular assessment curriculum for advanced practice nurses at four institutions. Each institution used a one-group pre-to-post-intervention design. Educational interventions included faculty-led, simulation-based case presentations using the Harvey® cardiopulmonary patient simulator (CPS), and independent learning sessions using the CPS and a multimedia, computer-based CD-ROM program. Outcome measures included a 31-item cognitive written exam, a 13-item skills checklist used in each of a three-station objective structured clinical exam, learner self-efficacy and satisfaction survey, instructor satisfaction and self-efficacy survey, and a participant logbook to record practice time using the self-learning materials. Thirty-six students who received the simulation-based training showed statistically significant pre-to-post-test improvement in cognitive knowledge and cardiovascular assessment skills.